The potential contribution of impaired brain glucose metabolism to congenital Zika syndrome - Gilbert-Jaramillo, J; Garcez, P; James, W; Molnár, Z; Clarke, K (Wiley, 2019)
The Zika virus (ZIKV) became a major worldwide public concern in 2015 due to the congenital syndrome which presents the highest risk during the first trimester of pregnancy and includes microcephaly and eye malformations. Several cellular, genetic and molecular studies have shown alterations in metabolic pathways, endoplasmic reticulum (ER) stress, immunity and dysregulation of RNA and energy metabolism both in vivo and in vitro. Here we summarise the main metabolic complications, with a particular focus on the possibility that brain energy metabolism is altered following ZIKV infection, contributing to developmental abnormalities. Brain energetic failure has been implicated in neurological conditions such as autism disorder and epilepsy, as well as in metabolic diseases with severe neurodevelopmental complications such as Glut‐1 deficiency syndrome. Therefore, these energetic alterations are of wide‐ranging interest as they might be directly implicated in congenital ZIKV syndrome. Data showing increased glycolysis during ZIKV infection, presumably required for viral replication, might support the idea that the virus can cause energetic stress in the developing brain cells. Consequences may include neuroinflammation, cell cycle dysregulation and cell death. Ketone bodies are non‐glycolytic brain fuels that are produced during neonatal life, starvation or fasting, ingestion of high‐fat low‐carbohydrate diets, and following supplementation with ketone esters. We propose that dietary ketones might alter the course of the disease and could even provide some degree of prevention of ZIKV‐associated abnormalities and potentially related neurological conditions characterised by brain glucose impairment.